2010
DOI: 10.1021/bc1000998
|View full text |Cite
|
Sign up to set email alerts
|

Optical Imaging of Bacterial Infection in Living Mice Using Deep-Red Fluorescent Squaraine Rotaxane Probes

Abstract: Two structurally related fluorescent imaging probes allow optical imaging of bacterial leg infection models in living athymic and immunocompetent mice. Structurally, the probes are comprised of a deep-red fluorescent squaraine rotaxane scaffold with two appended bis(zinc(II)-dicolylamine) (bis(Zn-DPA)) targeting ligands. The bis(Zn-DPA) ligands have high affinity for the anionic phospholipids and related biomolecules that reside within the bacterial envelope, and they are known to selectively target bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 56 publications
2
64
0
Order By: Relevance
“…This is exemplified by the decrease in luminescence that has been observed when many luxexpressing bacterial species, such as Bifidobacterium, 38 enter stationary phase during in vitro growth. [46][47][48] Bioluminescent bacteria have been used extensively to study a diverse range of biological processes such as infection, 49 quorum sensing 50 and gene expression. 51 However, the employment of luciferase or lux tagged bacterial strains as gene delivery vehicles for the treatment of cancer is an emerging field.…”
Section: Bioluminescence Imaging (Bli)mentioning
confidence: 99%
“…This is exemplified by the decrease in luminescence that has been observed when many luxexpressing bacterial species, such as Bifidobacterium, 38 enter stationary phase during in vitro growth. [46][47][48] Bioluminescent bacteria have been used extensively to study a diverse range of biological processes such as infection, 49 quorum sensing 50 and gene expression. 51 However, the employment of luciferase or lux tagged bacterial strains as gene delivery vehicles for the treatment of cancer is an emerging field.…”
Section: Bioluminescence Imaging (Bli)mentioning
confidence: 99%
“…During apoptosis, phosphatidylserine (PS) externalized to the surface of neutrophils provides a specific biomarker for the detection of infection and inflammation [12,23]. Previous studies have reported that synthetic bis(zinc(II)-dipicolylamine) (DPAZn2) coordination complexes possess a selective affinity for biomembranes enriched with PS [10], and fluorescence-labeled bis(zinc(II)-dipicolylamine) coordination complexes have been used for in vivo optical imaging of bacterial abscesses with a contribution from PS fluorescence [12,13,24]. However, this method presents significant challenges for imaging those lesions that are deeply seated in the body, since emitted light photons may not penetrate the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic bis(zinc (II)-dipicolylamine) coordination complexes (DPAZn2) are the best known compounds with the potential to binding PS, and some fluorescent DPAZn2 analogues have been used for optical imaging of cell death with the same target as Annexin V [10,11]. In addition, optical imaging with fluorescent DPAZn2 analogues has also been used to detect the infectious tissues induced with bacterial or nonbacterial pathway [12,13]. However, optical imaging has poor tissue penetration, which limits the use of optical probes for in vivo imaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…Smith has developed a range of bis-ZnDPA complexes as probes able to recognise apoptotic and bacterial cells, which they have demonstrated with considerable success both in vitro (liposomal models and cells) 14,15 and in small animal tumour and bacterial infection models, using NIR optical imaging. 16,17 In a recently-published study we showed that bis-ZnDPA, lanthanide complexes [Ln(L)Zn 2 ](NO 3 ) 4 (Ln = Gd, Eu; see Scheme 1), bind strongly to polyanionic species, including Fmoc-phosphoserine. 18 This prompted us to study whether this complex might also bind bisanionic phosphoserine head groups at membrane surfaces.…”
mentioning
confidence: 99%
“…This selectivity is consistent with the high selectivity for apoptotic cells previously reported in a wide and structurally diverse range of bis-(Zn-DPA) complexes. 14,15,17 As such…”
mentioning
confidence: 99%